Aplikasi Radio Online pada PT. Radio Swara Mersidiona 93.9 FM - Darussalam, Muhammad; Susila, Mochamad Nandi; Maruloh, Maruloh (LPPM STMIK ANTAR BANGSA, 2019)
Abstract—Digital audio technology has entered its peak along with the development of the internet world today. One of the special concern of researchers, namely the field of radio broadcasting, where previously only be heard through conventional radio devices. The focus of this study, discussed about the design of the online radio application on one of the leading radio station Mersi 93.9 FM, so it has the purpose to help the optimization of the broadcasting activities are carried out because it was based digital applications that can be accessed through a device that is connected to the internet. The method of application development using the waterfall model by utilizing a graphical method also in the form of a collection of diagrams for visualization and documentation in the coverage UML diagram (Unified Modelling Language). While supporting the writing source code for applications researchers aided by CodeIgniter framework. Stages of testing an application is performed using black box testing testing techniques. The results of the research that has been done, that the applications are designed to wake up has helped increase the competitiveness of Mersi 93.9 FM in broadcasting activities, as well as radio-party clients to easily promote products owned. Intisari—Teknologi digital audio telah memasuki masa puncaknya seiring dengan perkembangan dunia internet saat ini. Salah satu yang menjadi perhatian khusus peneliti yaitu bidang penyiaran radio, dimana sebelumnya hanya dapat didengar melalui perangkat radio konvensional. Fokus penelitian ini, dibahas mengenai perancangan aplikasi radio online pada salah satu stasiun radio terkemuka yaitu Mersi 93.9 FM, sehingga memiliki tujuan agar dapat membantu optimalisasi aktifitas kegiatan penyiaran yang dilakukan karena sudah berbasis digital aplikasi yang bisa diakses melalui perangkat yang terkoneksi internet. Metode pengembangan aplikasi menggunakan waterfall model dengan memanfaatkan pula metode grafis berupa kumpulan diagram-diagram untuk visualisasi dan dokumentasi dalam cakupan diagram UML (Unified Modelling Language). Sementara untuk penunjang penulisan kode sumber aplikasi peneliti dibantu oleh framework CodeIgniter. Tahapan pengujian aplikasi dilakukan dengan menggunakan teknik pengujian black box testing. Hasil dari penelitian yang telah dilakukan, bahwa aplikasi yang dirancang bangun telah membantu meningkatkan daya saing Mersi 93.9 FM dalam aktifitas penyiarannya, serta klien pihak radio yang dengan mudah mempromosikan produk yang dimiliki.Kata Kunci — Radio Online, Mersi 93.9 FM, UML